2000
DOI: 10.1097/00000542-200011000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pump Prime in the Etiology and Pathogenesis of Cardiopulmonary Bypass–associated Acidosis

Abstract: Cardiopulmonary bypass-induced metabolic acidosis appears to be iatrogenic in nature and derived from the effect of pump prime fluid on acid-base balance. The extent of such acidosis and its duration varies according to the type of pump prime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
86
1
7

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(99 citation statements)
references
References 0 publications
4
86
1
7
Order By: Relevance
“…With our inclusion and exclusion criteria in our study and with the type of surgery we limited the causes of metabolic acidosis to two: dilutional acidosis and lactic acidosis. Recent studies have proposed dilutional acidosis as an explanation for low BD after CPB [14,15,16,17]. Indeed the hydric balance during CPB in our study averaged 2000 ml, comprising cristalloid (Ringer's latacte) and colloid (6% hydroxyethyl starch solution).…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…With our inclusion and exclusion criteria in our study and with the type of surgery we limited the causes of metabolic acidosis to two: dilutional acidosis and lactic acidosis. Recent studies have proposed dilutional acidosis as an explanation for low BD after CPB [14,15,16,17]. Indeed the hydric balance during CPB in our study averaged 2000 ml, comprising cristalloid (Ringer's latacte) and colloid (6% hydroxyethyl starch solution).…”
Section: Discussionsupporting
confidence: 45%
“…Despite the difference between the two groups in the hydric balance during CPB, the mean volume difference was not very large (1936±581 ml in group A, 2159±620 ml for group B). Liskaser et al [17] found decreased base immediately after the pump prime, with normalization of BD at the end of the procedure. A low BD value 1 h after the end of the procedure cannot be explained by the pump prime dilution.…”
Section: Discussionmentioning
confidence: 97%
“…Although common causes of metabolic acidosis, such as lactic acidosis and renal failure, may be unavoidable, often the source of metabolic acidosis is at least partly iatrogenic, because saline resuscitation is often used to treat shock. Large-volume saline infusion produces metabolic acidosis by increasing the plasma Cl Ϫ concentration relative to the plasma Na ϩ concentration (18,27,31,32,41,42). The result is a reduction in the strong ion difference, the difference between positively and negatively charged electrolytes, which in turn produces an increase in free H ϩ to preserve electrical neutrality (38).…”
Section: Discussionmentioning
confidence: 99%
“…However, different studies have used different acids to lower pH o , and no studies have compared the effects of different forms of clinically relevant acidosis on the immune response. Because critically ill and injured patients may be adversely affected by even short-term alterations in the immune response (augmentation and attenuation) and because some forms of metabolic acidosis are largely iatrogenic (18,27,31,32,41,42), we believe that it is necessary to characterize the effects of acidosis on the immune response. We further believe that it is imperative that the mechanisms responsible for these effects be elucidated.…”
mentioning
confidence: 99%
“…A dministration of resuscitation fluids has been associated with the development of metabolic acidosis, the clinical significance of which remains uncertain (1)(2)(3)(4)(5). In such studies, however, large amounts of fluids were given for short periods of time (1)(2)(3)(4)(5).…”
mentioning
confidence: 99%